Synthesis and stereochemistry of highly crowded N-benzylpiperidones - Dindulkar, Someshwar D.; Parthiban, Paramasivam; Puranik, Vedavati G.; Jeong, Yeon Tae (Journal of Molecular Structure, 2012)
A series of N-benzylated 3,5-diakyl-2,6-diarylpiperidin-4-ones 4-8 were conveniently synthesized in significant yields of 68-88% by N-benzylation of the corresponding 2,6-diaryl-3,5-dimethylpiperidin-4-ones 1-3 using different benzyl bromides. Initially, the new piperidone 2,6-bis(4-ethoxypheny1)-3,5-dimethylpiperidin-4-one 3 was synthesized by the condensation of 1:1:2 M ratio of 3-pentanone, ammonium acetate and para-ethoxybenzaldehyde in ethanolic medium. All the synthesized new compounds 3-8 were characterized by their analytical and spectral (IR, H-1 and C-13 NMR) interpretations. The stereochemistry of the new piperidone 3 was elucidated as chair conformation with an equatorial orientation of all substituents, suggested by its vicinal couplings from H-1 NMR spectrum. To investigate the impact on piperidone stereochemistry as well as NMR chemical shifts, all the N-benzylated products 4-8 were compared with their corresponding precursors, and as a result, it is clearly established that all the synthesized N-benzyl piperidones exist in the chair conformation with an equatorial orientation of all the substituents at C-2, C-3, C-5, C-6 and N. Contrary to the probability all N-benzylated compounds retain the same conformation and configuration as their precursors, however, a remarkable change on the chemical shifts are observed. For the further unambiguous confirmation of stereochemistry, the 1-benzyl-3,5-dimethyl-2,6-diphenylpiperidin-4-one 4 was examined by single-crystal X-ray diffraction. The compound 4, C26H27NO, crystallized in a P-1 space group under triclinic system with unit cell dimensions a, b, c (angstrom) and alpha, beta, gamma (degrees) of 10.156(2), 11.002(2), 11.348(4) and 116.74(4), 100.81(3), 100.17(3), respectively. (C) 2011 Elsevier B.V. All rights reserved.
Keywords: Chair conformation; Configuration; crystal structure; N-benzylation; NMR; Piperidin-4-one